Performance of organic manures alone or combined with chemical fertilizers in increasing growth, yield, and nutritional quality of potatoes in the Eastern part of Türkiye - Kurt, Gunes; Ozturk, Erdogan; Sefaoglu, Fırat; Gul, Volkan; Toktay, Zehra; Mosber, Goltay (Informa UK Limited, 2024)
This study aimed to determine the effects of different types of fertilizers (organic and inorganic fertilizers) on plant growth, yield, and yield components of potatoes grown in the high-altitude plateau of eastern Turkiye in 2017 and 2019. In the experiment, single or combined doses of nitrogen (N; as ammonium sulfate) and phosphorus (P; as triple super phosphate) as inorganic fertilizers and leonardite (L) and vermicompost (V) fertilizers as organic fertilizers were used. In both years, different fertilizer treatments significantly affected plant growth, yield, and yield components. Tuber yield per hill (941.0 g), marketable tuber yield (32.71 t ha(-1)), total tuber yield (37.84 t ha(-1)), specific gravity (1. 077 g cm(-3)), chip productivity (35.9%), starch (13.03%) and protein (11.0%) ratios increased when N fertilizer was used in combination with vermicompost or leonardite. N fertilizer combined with V or L fertilizer increased tuber yield under harsh continental climates, short growth periods, and high altitudes.
Keywords: organic fertilizer; Inorganic fertilizer; Solanum tuberosum; yield components